Learning from Chatting: How Our Virtual Reference Questions Are Giving Us Answers - Rourke, Lorna; Lupien, Pascal (Evidence Based Library and Information Practice, 2010)
Objective - This research compares two types of online reference services and attempts to determine whether the same sorts of questions are being asked; which questions are being asked most often; and whether patron and staff behaviour is consistent or different in the two types of online reference sessions. Patron satisfaction with the two types of online reference services is also examined. Methods - The researchers reviewed over 1400 online reference transcripts, including 744 from Docutek virtual reference (VR) transactions and 683 from MSN chat reference (IM) transactions. The questions were classified according to categories of reference questions based on recurring questions discovered during the review. Each transaction was also categorized as "informal" or "formal" based on patron language and behaviour, and general observations were made about the interactions between patrons and librarians. In addition, results from 223 user surveys were examined to determine patron satisfaction with online reference services and to determine which type of service patrons preferred. Results - The analysis suggests that patrons are using VR and IM services differently. In general, VR questions tend to be more research intensive and formal, while IM questions are less focused on academic research and informal. Library staff and patrons appear to alter their behaviour depending upon which online environment they are in. User surveys demonstrated that patrons are generally satisfied with either type of online reference assistance. Conclusion - Both types of online reference service are meeting the needs of patrons. They are being used for different purposes and in different ways, so it may be worthwhile for libraries to consider offering both VR and IM reference. The relationship building that appears to take place more naturally in IM interactions demonstrates the benefits of librarians being more approachable with patrons in order to provide a more meaningful service.